[13C3, 15N1]-labeled isodesmosine: A potential internal standard for LC–MS/MS analysis of desmosines in elastin degradation. Issue 10 (15th May 2015) - Tanigawa, Takahiro; Komatsu, Akira; Usuki, Toyonobu
Graphical abstract